1998
DOI: 10.1017/s0022112098008702
|View full text |Cite
|
Sign up to set email alerts
|

The Earth's rotation and laminar pipe flow

Abstract: A pipe flow facility with a length of 32 m and a diameter of 40 mm has been designed in which a laminar flow of water can be maintained for Reynolds numbers up to 60 000. Velocity measurements taken in this facility show an asymmetric velocity profile both in the vertical as well as horizontal direction with velocities that deviate strongly from the parabolic Hagen–Poiseuille profile. The cause of this asymmetry is traced back to the influence of the Earth's rotation. This is confirmed by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 4 publications
3
17
0
Order By: Relevance
“…This is due to an increase in laminar velocity profile asymmetry, the level of distortion being higher for Ek = 1. Given the previous results of Draad & Nieuwstadt (1998) and the excellent agreement between experiment and simulation here for two different Ekman numbers, we conclude that Coriolis forces can be significant in fully developed laminar square duct flow, especially for water. As a consequence, all of the data which follows is for 50 % glycerol/water solution (Ek ≈ 7).…”
Section: Experimental Studiessupporting
confidence: 86%
See 2 more Smart Citations
“…This is due to an increase in laminar velocity profile asymmetry, the level of distortion being higher for Ek = 1. Given the previous results of Draad & Nieuwstadt (1998) and the excellent agreement between experiment and simulation here for two different Ekman numbers, we conclude that Coriolis forces can be significant in fully developed laminar square duct flow, especially for water. As a consequence, all of the data which follows is for 50 % glycerol/water solution (Ek ≈ 7).…”
Section: Experimental Studiessupporting
confidence: 86%
“…This deviation from the analytical solution is surprising as the velocity fluctuations remain very low (about 2 %), indicating that the flow is laminar (see figure 3(b); the fluctuations, which ideally should be zero, can be attributed to the measurement noise of the LDV system). We believe this deviation of the observed U /U b from the analytical solution can be ascribed to Coriolis effects due to the Earth's rotation as has been observed previously in pipe flows by Draad & Nieuwstadt (1998). They showed that the effect of rotation on a fully developed laminar flow can be estimated using the Ekman number, a ratio of viscous to Coriolis forces:…”
Section: Experimental Studiesmentioning
confidence: 56%
See 1 more Smart Citation
“…One example is high-precision measurements of the velocity profile of laminar flow in a long pipe [15]. It was found that the expected parabolic profile of the velocity field was skewed by the Earth's rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, subsequent modelling work has focused on the wide-channel analytical model that forms the basis for the work reported here. The fuller model can be a powerful tool to understand quantitatively the deviations from infinite width flow behaviour in actual finite-width rotating spiral channels, including the well-known Coriolis secondary flows (Mori and Nakayama, 1968;Miyazaki, 1971;Draad and Nieuwstadt, 1998;Ishigaki, 1999;Lee and Baek, 2002).…”
Section: Discussionmentioning
confidence: 99%